Low‐Temperature Synthesis, Characterization, and Stability of Spinel‐Type Li2NiF4 and Solid‐Solutions Li2Ni1–xCoxF41. Issue 2 (18th December 2012) - Kohl, Julia; Nakhal, Suliman; Ferro, Noel; Bottke, Patrick; Wilkening, Martin; Bredow, Thomas; Heitjans, Paul; Lerch, Martin
Abstract A new synthesis route to Li2NiF4 based on a fluorolytic process using Ni(acac)2 or Ni(OAc)2·4H2O as precursor is presented. Variation of the synthesis conditions allows crystallite size control of the obtained powders. 6Li and 7Li MAS NMR experiments were carried out to study local environments of the lithium ions. Several attempts were made to synthesize Li2CoF4, which are, unfortunately, hitherto not successful. Nevertheless, our studies clearly reveal that solid solutions Li2NiF4–Li2CoF4 are stable up to ca. 30 % cobalt. High‐temperature X‐ray diffraction measurements also show no evidence for the existence of pure Li2CoF4. These findings are supported by quantum chemical calculations.